Potensi Kayu Apu (Pistia stratiotes) di Perairan Danau Tempe Kabupaten Wajo, Sulawesi Selatan sebagai Agen Fitoremediasi terhadap Ion Logam Cu2+ - Nasir, Muhammad; Pandiangan, Dingse; Marlein Mambu, Susan; Nur, Muhummad; Fauziah, Siti; Insani Amir, Nur; Irfandi, Rizal; Rahim, Sahriah (Al-Kimia, 2021)
Lake Tempe is a technical lake that stretches across three districts in South Sulawesi, namely Wajo Regency, Sidendang Rappang Regency and Soppeng Regency. Because of its vastness, people use the lake for various activities, one of which is the textile industry. The textile industry uses a lot of chemicals which are then dissolved in water. These materials contain suspended solids, organic substances and heavy metals. The washing stage is the final process of the textile industry. The waste product is liquid waste containing heavy metals, including copper (Cu). To reduce or remove Cu metal found in Tempe Lake, phytoremediation techniques are used. Phytoremediation is an effort made to remove hazardous substances in areas contaminated with waste by using plants that have phytoremediator properties. Water plants that can be used are apu wood (Pistia stratiotes). The purpose of this study was to determine the ability of apu (Pistia stratiotes) to remediate Cu2 + in contaminated Lake Tempe water. The research method used included: Cu2+ assay, physicochemical analysis, Bio-Concentration Factor (BCF) and identification of functional groups. The greatest adsorbed Cu metal ion on apu wood is on the 10th day of 100,274 mg / Kg.